Adhesion Properties of Acrylonitrile-Butadiene Rubber/Standard Malaysian Rubber Blend Based Pressure-Sensitive Adhesive - Poh, B. T.; Lamaming, J.; Tay, G. S. (Hindawi Publishing Corporation, 2014)
Viscosity and adhesion properties of NBR/SMR L blend based pressure-sensitive adhesive were investigated using coumaroneindene resin, toluene, and poly(ethylene terephthalate) (PET) as tackifier, solvent, and coating substrate, respectively. Coumaroneindene resin content was fixed at 40 parts per hundred parts of rubber (phr) in the adhesive formulation.The ratio of NBR/SMR L blend used was 0, 20, 40, 60, 80, and 100% of NBR content. Four different thicknesses, that is, 30, 60, 90, and 120